Proteomic analysis reveals temporal changes in protein expression in human induced pluripotent stem cell-derived cardiomyocytes in vitro - Hellen,N; Pinto,Ricardo C; Vauchez,K; Whiting,G; Wheeler,J; Harding,SE (Stem Cells and Development, 2019)
Human induced pluripotent stem cell-derived cardiomyocytes hold great promise for regenerative medicine and in vitro screening. Despite displaying key cardiomyocyte phenotypic characteristics, they more closely resemble foetal/neonatal cardiomyocytes and further characterisation is necessary. Combining the use of tandem mass tags to label cell lysates, followed by multiplexing, we have determined the effects of short term (30 day) in vitro culture on human induced pluripotent stem cell derived cardiomyocyte protein expression. We found that human induced pluripotent stem cell derived cardiomyocytes exhibit temporal changes in global protein expression; alterations in protein expression were pronounced during the first 2 weeks following thaw and dominated by reductions in proteins associated with protein synthesis and ubiquitination. Between 2 and 4 weeks proceeding thaw alterations in protein expression were dominated by metabolic pathways, indicating a potential temporal metabolic shift from glycolysis towards oxidative phosphorylation. Time-dependent changes in proteins associated with cardiomyocyte contraction, excitation-contraction coupling and metabolism were detected. While some were associated with expected functional outcomes in terms of morphology or electrophysiology, others such as metabolism did not produce the anticipated maturation of human induced pluripotent stem cell derived cardiomyocytes. In several cases, a predicted outcome was not clear because of the concerted changes in both stimulatory and inhibitory pathways. Nevertheless, clear development of human induced pluripotent stem cell derived cardiomyocytes over this time period was evident.